Measurement of theta(13) in Double Chooz using neutron captures on hydrogen with novel background rejection techniques - Abe, Y.; Appel, S.; Abrahao, T.; Almazan, H.; Alt, C.; dos Anjos, J. C.; Barriere, J. C.; Baussan, E.; Bekman, I.; Bergevin, M.; Horton-Smith, Glenn (My University, 2016)
The Double Chooz collaboration presents a measurement of the neutrino mixing angle theta(13) using reactor (nu) over bar (e) observed via the inverse beta decay reaction in which the neutron is captured on hydrogen. This measurement is based on 462.72 live days data, approximately twice as much data as in the previous such analysis, collected with a detector positioned at an average distance of 1050m from two reactor cores. Several novel techniques have been developed to achieve significant reductions of the backgrounds and systematic uncertainties. Accidental coincidences, the dominant background in this analysis, are suppressed by more than an order of magnitude with respect to our previous publication by a multi-variate analysis. These improvements demonstrate the capability of precise measurement of reactor (nu) over bar (e) without gadolinium loading. Spectral distortions from the (nu) over bar (e) reactor flux predictions previously reported with the neutron capture on gadolinium events are confirmed in the independent data sample presented here. A value of sin(2) 2 theta(13) = 0.095(0.039)(+0.039)(stat+syst) is obtained from a fit to the observed event rate as a function of the reactor power, a method insensitive to the energy spectrum shape. A simultaneous fit of the hydrogen capture events and of the gadolinium capture events yields a measurement of sin(2) 2 theta(13) = 0.088 +/- 0.033(stat+syst).
Citation: Abe, Y., Appel, S., Abrahao, T., Almazan, H., Alt, C., dos Anjos, J. C., . . . Double Chooz, C. (2016). Measurement of theta(13) in Double Chooz using neutron captures on hydrogen with novel background rejection techniques. Journal of High Energy Physics(1), 29. doi:10.1007/jhep01(2016)163
Additional Authors: Buck, C.;Busenitz, J.;Cabrera, A.;Camilleri, L.;Carr, R.;Cerrada, M.;Chauveau, E.;Chimenti, P.;Collin, A. P.;Conrad, J. M.;Crespo-Anadon, J. I.;Crum, K.;Cucoanes, A. S.;Damon, E.;Dawson, J. V.;Dhooghe, J.;Dietrich, D.;Djurcic, Z.;Dracos, M.;Etenko, A.;Fallot, M.;von Feilitzsch, F.;Felde, J.;Fernandes, S. M.;Fischer, V.;Franco, D.;Franke, M.;Furuta, H.;Gil-Botella, I.;Giot, L.;Goger-Neff, M.;Gomez, H.;Gonzalez, L. F. G.;Goodenough, L.;Goodman, M. C.;Haag, N.;Hara, T.;Haser, J.;Hellwig, D.;Hofmann, M.;Horton-Smith, G. A.;Hourlier, A.;Ishitsuka, M.;Jochum, J.;Jollet, C.;Kaether, F.;Kalousis, L. N.;Kamyshkov, Y.;Kaneda, M.;Kaplan, D. M.;Kawasaki, T.;Kemp, E.;de Kerret, H.;Kryn, D.;Kuze, M.;Lachenmaier, T.;Lane, C. E.;Lasserre, T.;Letourneau, A.;Lhuillier, D.;Lima, H. P.;Lindner, M.;Lopez-Castano, J. M.;LoSecco, J. M.;Lubsandorzhiev, B.;Lucht, S.;Maeda, J.;Mariani, C.;Maricic, J.;Martino, J.;Matsubara, T.;Mention, G.;Meregaglia, A.;Miletic, T.;Milincic, R.;Minotti, A.;Nagasaka, Y.;Navas-Nicolas, D.;Novella, P.;Oberauer, L.;Obolensky, M.;Onillon, A.;Osborn, A.;Palomares, C.;Pepe, I. M.;Perasso, S.;Porta, A.;Pronost, G.;Reichenbacher, J.;Reinhold, B.;Rohling, M.;Roncin, R.;Rybolt, B.;Sakamoto, Y.;Santorelli, R.;Schilithz, A. C.;Schonert, S.;Schoppmann, S.;Shaevitz, M. H.;Sharankova, R.;Shrestha, D.;Sibille, V.;Sinev, V.;Skorokhvatov, M.;Smith, E.;Soiron, M.;Spitz, J.;Stahl, A.;Stancu, I.;Stokes, L. F. F.;Strait, M.;Suekane, F.;Sukhotin, S.;Sumiyoshi, T.;Sun, Y.;Svoboda, R.;Terao, K.;Tonazzo, A.;Thi, H. H. T.;Valdiviesso, G.;Vassilopoulos, N.;Veyssiere, C.;Vivier, M.;Wagner, S.;Walsh, N.;Watanabe, H.;Wiebusch, C.;Wurm, M.;Yang, G.;Yermia, F.;Zimmer, V.;Double Chooz, Collaboration
Keywords: Oscillation; Electroweak Interaction; Neutrino Detectors And Telescopes; Flavor Physics; Fission-Products; Spectra